Number 7 (January 1979) - Southern Fishes Council (Southeastern Fishes Council Proceedings, 1979)
Whatever Happened to the Silvery Minnow (Hybognathus nuchalis) in the Tennessee River? By D.A. Etnier et al., plus News Notes, 4 pp.
Keywords: fishes; Silvery Minnow; Hybognathus nuchalis; Tennessee River